Effect of Temperature on Moisture Content in Kernel (Palm Core) in Seed Silo by Complete Random Design Method (RAL) in Kernel Crushing Plant Unit of PT. Smart Tbk, Belawan - Agfira, Utami Nanda; Harahap, Bonar; Sibuea, Siti Rahmah (Jurnal Teknik Indonesia, 2024)
The moisture content in palm kernels is one of the crucial factors influencing the quality and productivity of palm oil production. This research aims to analyze the effect of temperature on the moisture content in palm kernels at the Seed Silo in the Kernel Crushing Plant Unit of PT. Smart Tbk, Belawan, using the Complete Randomized Design (CRD) method and Simple Linear Regression. The kernels were collected from several plots of oil palm plantations spread across certain areas. In the process, it is essential to understand how temperature affects the moisture content in the kernels. The study was conducted with four repetitions for each experiment to determine the moisture content analysis data of the kernels in the Seed Silo. The results of the moisture content reduction calculations showed an optimum temperature of 100°C with the lowest moisture content of 6.26%. Based on the Complete Randomized Design (CRD) method, the results showed that the F-calculated value of 3.12 was greater than the F-table value of 2.95, meaning that H0 was rejected (temperature does not affect moisture content) and H1 was accepted (temperature affects moisture content). It can be concluded that the experiments at each given temperature significantly affected the resulting moisture content. Then, using the Simple Linear Regression method, a correlation coefficient value of -1.00 was obtained, indicating a perfect negative correlation between temperature (X) and moisture content (Y). The coefficient value indicates the strength of the relationship between variables X and Y. Simple linear regression shows that the higher the temperature, the lower the moisture content in the palm kernels. The practical implications can include recommendations for optimal temperature settings in the handling and processing of palm kernels to improve the quality and productivity of the production output.